2020
DOI: 10.1097/ogx.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of Human Ovarian Cortex Identifies Distinct Cell Populations But No Oogonial Stem Cells

Abstract: The human ovary orchestrates sex hormone production and undergoes monthly structural changes to release mature oocytes. The outer lining of the ovary (cortex) has a key role in defining fertility in women as it harbors the ovarian reserve. It has been postulated that putative oogonial stem cells exist in the ovarian cortex and that these can be captured by DDX4 antibody isolation. Here, we report single-cell transcriptomes and cell surface antigen profiles of over 24,000 cells from high quality ovarian cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 63 publications
(123 reference statements)
2
74
0
Order By: Relevance
“…These contrasting studies suggest other possible explanations for the observations made in Zou et al (2009) and White et al (2012) including culture‐induced de‐differentiation of the isolated cells into putative stem cells, but were unable to validate the presence of any mitotically active germline stem cells in postnatal ovaries. The presence of germline stem cells has also been explored in human ovaries, but without evidence for the existence of these cells (Wagner et al, 2020).…”
Section: Perspectivesmentioning
confidence: 99%
“…These contrasting studies suggest other possible explanations for the observations made in Zou et al (2009) and White et al (2012) including culture‐induced de‐differentiation of the isolated cells into putative stem cells, but were unable to validate the presence of any mitotically active germline stem cells in postnatal ovaries. The presence of germline stem cells has also been explored in human ovaries, but without evidence for the existence of these cells (Wagner et al, 2020).…”
Section: Perspectivesmentioning
confidence: 99%
“…This higher speed does not affect the stem cells as they have minimal cytoplasm. This is the basic issue with study reported by Wagner et al 1 where they did all processing at 300 g as mentioned in their Material and Methods section. Like Wagner's group, even Tilly's group uses 300 g to study OSCs but suggest to increase speed to 600 g if number of DDX-4 positive cells is not enough [18].…”
mentioning
confidence: 87%
“…The controversy surrounding ovarian stem cells does not seem to end. Recently a group from Karolinska Institute, Sweden carried out single-cell RNA-seq and transcriptome analysis to study human ovarian cortical tissue and concluded that it does not harbor stem cells and rather comprises six distinct cell types including oocytes, granulosa cells, immune cells, endothelial cells, perivascular cells, and stromal cells [1]. On the contrary, ovary harbors two populations of stem cells including pluripotent, 2-6 μm, very small embryonic-like stem cells (VSELs) and 6-8 μm ovarian stem cells (OSCs) [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations